Perbedaan Persiapan Siswa yang Hasil Belajar Tinggi dan Rendah dalam Menghadapi Ujian Nasional - Linda Fitria (Jurnal Konseling dan Pendidikan, 2013)
To  pass the examination, the most important thing to be considered by the students is the examination preparation. There are so many kinds of examination faced by the students, one of it is national examination. Therefore, the national examination should be prepared well by the students, school, and parents since it is a tool to measure students competency of achievement which held by education unit in order to obtain learning confession and it is a requirement of finishing education level. This research is aimed to describe and differentiate the preparation of students with high learning achievement and the students with low learning achievement in facing national examination. This is a comparative quantitative descriptive approach supported with interview. The target of the research is students of SMA Adabiah Padang of academic year 2012/2013, with 327 students as the population. There are 80 students placed as sample. The research finding reveals that (1) physical preparation of students with high learning achievement and the students with low learning achievement in facing national examination is in well prepared category (2) psychology preparation for both students with high learning achievement and the students with low learning achievement is in well prepared category, (3) the preparation in mastering the learning material for both students with high learning achievement and the students with low learning achievement is in well prepared category,(4) the analysis of t test result reveals that there is a significant difference between students with high learning achievement and the students with low learning achievement of SMA Adabiah Padang